Association of estimated dietary acid load with albuminuria in Japanese adults: a cross-sectional study - Keiko Kabasawa; Michihiro Hosojima; Ribeka Takachi; Kazutoshi Nakamura; Yumi Ito; Akihiko Saito; Norie Sawada; Shoichiro Tsugane; Junta Tanaka; Ichiei Narita (BMC Nephrology, 2019)
Abstract Background Acid-base imbalance might promote the progression of chronic kidney disease (CKD), but whether nutrient-derived dietary acid load increases the risk of albuminuria or even high normoalbuminuria is unclear. Methods A Japanese cohort comprising 3250 men and 3434 women aged 40–97 years with urine albumin-to-creatinine ratio (ACR) < 33.9 mg/mmol or estimated glomerular filtration rate ≥ 15 ml/min/1.73 m2 were assessed. We performed a cross-sectional evaluation of the association between net endogenous acid production (NEAP), estimated as dietary protein to potassium content ratio, and the presence of high normoalbuminuria (ACR: 1.13–3.38 mg/mmol) or microalbuminuria. Results Median NEAP was 43.4 (interquartile range (IQR): 34.2–53.4) mEq/day in men and 35.0 (IQR: 27.7–43.6) mEq/day in women. Median ACR was 1.11 (IQR: 0.57–2.49) mg/mmol in men and 1.47 (IQR: 0.82–2.83) mg/mmol in women. In multivariate analysis, the adjusted odds ratio of the highest versus lowest NEAP quartile for microalbuminuria was 1.47 (95% confidence interval (CI): 1.08–1.99) in men and 1.54 (95% CI: 1.11–2.14) in women. For high normoalbuminuria or microalbuminuria, the adjusted odds ratio was 1.28 (95% CI: 1.02–1.59) in men and 1.39 (95% CI: 1.11–1.74) in women. From nutrient composition analysis, subjects with the highest potassium intake, but not protein intake, had lower adjusted odds ratios for the presence of microalbuminuria than those in the lowest quartile for potassium intake. Conclusions Higher NEAP was associated with albuminuria and its association might negatively relate to potassium intake in an adult Japanese population.